A structural and dynamic model for the assembly of Replication Protein A on single-stranded DNA. Issue 1 (December 2018) - Yates, Luke; Aramayo, Ricardo; Pokhrel, Nilisha; Caldwell, Colleen; Kaplan, Joshua; Perera, Rajika; Spies, Maria; Antony, Edwin; Zhang, Xiaodong
Abstract Replication Protein A (RPA), the major eukaryotic single stranded DNA-binding protein, binds to exposed ssDNA to protect it from nucleases, participates in a myriad of nucleic acid transactions and coordinates the recruitment of other important players. RPA is a heterotrimer and coats long stretches of single-stranded DNA (ssDNA). The precise molecular architecture of the RPA subunits and its DNA binding domains (DBDs) during assembly is poorly understood. Using cryo electron microscopy we obtained a 3D reconstruction of the RPA trimerisation core bound with ssDNA (∼55 kDa) at ∼4.7 Å resolution and a dimeric RPA assembly on ssDNA. FRET-based solution studies reveal dynamic rearrangements of DBDs during coordinated RPA binding and this activity is regulated by phosphorylation at S178 in RPA70. We present a structural model on how dynamic DBDs promote the cooperative assembly of multiple RPAs on long ssDNA. Replication Protein A (RPA) coats single stranded DNA (ssDNA) generated during DNA recombination, replication and repair. Here the authors present a structural model suggesting how RPA's DNA-binding domains promote cooperative assembly of multiple RPAs on long ssDNA.